Diffusion of metronidazole through human skin and synthetic membranes [Metronidazolün insan derisi ve sentetik membranlardan difüzyonu] - (:unkn) unknown (University of Istanbul, 2011)
The aim of this study was to evaluate the diffusion rate of metronidazole through human skin and different synthetic membranes. Metronidazole is a drug used in the treatment of infections caused by anaerobic bacteria, also used in vaginal infections, antibiotic-associated pseudo-membraneous colitis, trichomoniasis and symptomatic amebiasis. Metronidazole has small molecular weight (171.16), low pKa value (2.62) and sparing solubility in different media and is chosen as a model drug in this study. Diffusion experiments were conducted using Franz diffusion cells and the related diffusion coefficients were calculated. The diffusion of metronidazole from aqueous and oily phases through human skin showed the same type of trendline as with the hydrophobic synthetic membrane (GVHP). Therefore, we can conclude that GVHP might be used to test drug permeation simulating the human skin.
Keywords: Diffusion; Human skin; Metronidazole; Synthetic membranes